2017
DOI: 10.1002/micr.30215
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of free tissue transfer as a nutrient flap for critical ischemic foot: A case report

Abstract: Microsurgical procedure of free tissue transfer in critical limb ischemia patients with large ulceration has already been established. The nutrient flap concept was that transferred tissue functioned not only to cover the skin defect but also as a supplementary blood supply to the ischemic lower leg. This report showed the justification for this concept, which was rarely discussed. A 58-year-old male patient with progressive forefoot gangrene caused by arteriosclerosis obliterans was presented. The distal bypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
2
8
0
2
Order By: Relevance
“…Previous reports regarding the nutrient flap had presented only still images of blood flow, without showing dynamic perfusion from the flap into the surrounding tissue. 1 , 2 , 3 , 4 , 5 In the present case, we were able to demonstrate dynamic blood migration from the flap to the adjacent ischemic tissue ( Supplementary Video ), which we considered evidence of a nutrient flap. However, we found that the method has a substantial risk of causing thrombotic occlusion of the bypass graft owing to the limited runoff route for the blood flow.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous reports regarding the nutrient flap had presented only still images of blood flow, without showing dynamic perfusion from the flap into the surrounding tissue. 1 , 2 , 3 , 4 , 5 In the present case, we were able to demonstrate dynamic blood migration from the flap to the adjacent ischemic tissue ( Supplementary Video ), which we considered evidence of a nutrient flap. However, we found that the method has a substantial risk of causing thrombotic occlusion of the bypass graft owing to the limited runoff route for the blood flow.…”
Section: Discussionsupporting
confidence: 57%
“…The concept of a “nutrient flap,” in which ischemic tissue is nourished by a transferred well-perfused flap, has been advocated for use since the early days of free flap procedures. 1 , 2 , 3 , 4 , 5 Nutrient flap transfer has been applied, especially for the treatment of no-option chronic limb-threatening ischemia (CLTI). However, even among the reported cases in which a nutrient flap was successfully applied, no study has reported the detection of the dynamic flow of nutritional vascular formation over the flap edge.…”
mentioning
confidence: 99%
“…This result shows that patients who underwent free flap surgery were able to not only sustain the increased oxygen tension level after percutaneous transluminal angioplasty but also augment it, further supporting the idea of the nutrient flap. 30,31,58 Although the time point is unclear as to when the transcutaneous partial pressure of oxygen level starts to drop after percutaneous transluminal angioplasty in the non–free flap group, the mean level of 32.9 mmHg at 6 months shows that oxygen level after percutaneous transluminal angioplasty was not sustained, despite the initial improvement, and gradually declined after the angioplasty. Therefore, in the free flap group, one can assume that the tissue oxygen level will start to decline on the surrounding tissue as well.…”
Section: Discussionmentioning
confidence: 99%
“…1 The free flap in such cases serves as a nutrient flap, which nourishes the ischemic area, promotes angioneogenesis, and provides soft tissue coverage. 5…”
Section: Discussionmentioning
confidence: 99%